RILP inhibits tumor progression in osteosarcoma via Grb10-mediated inhibition of the PI3K/AKT/mTOR pathway - Zhun Wei; Kezhou Xia; Di Zheng; Changtian Gong; Weichun Guo (BMC, 2023)
Abstract Background Rab-interacting lysosomal protein (RILP) contains an alpha-helical coil with an unexplored biological function in osteosarcoma. This study investigated the expression of RILP in osteosarcoma cells and tissues to determine the effect of RILP on the biological behaviors of osteosarcoma cells and the underlying mechanism. Methods Tumor Immune Estimation Resource (TIMER) database, The Cancer Genome Atlas (TCGA) database and Gene Expression Omnibus (GEO) database were used for bioinformatic analysis. Co-immunoprecipitation experiment was used to determine whether the two proteins were interacting. In functional tests, cell counting kit-8 (CCK-8) assay, colony formation assay, wound healing assay, transwell invasion assay, Immunofluorescence (IF) assay and immunohistochemical (IHC) assay were performed. Results Overexpression of RILP significantly inhibited proliferation and impaired metastasis ability of osteosarcoma cells, while silencing of RILP showed the opposite trend. RNA-seq data analysis was applied in 143B cells and pathway enrichment analysis revealed that differentially expressed genes were mainly enriched in the PI3K/AKT pathway. We further verified that overexpression of RILP restrained the PI3K/AKT/mTOR signaling pathway and induced autophagy in osteosarcoma cells, while the opposite trend was observed when PI3K pathway activator 740Y-P was used. 3-Methyladenine (3-MA), a selective autophagy inhibitor, partially attenuated the inhibitory effect of RILP on the migration and invasion ability of osteosarcoma cells, suggesting the involvement of autophagy in epithelial-mesenchymal transition regulation in osteosarcoma cells. Growth factor receptor binding protein-10 (Grb10), an adaptor protein, was confirmed as a potential target of RILP to restrain the PI3K/AKT signaling pathway. We subcutaneously injected stably overexpressing 143B osteosarcoma cells into nude mice and observed that overexpression of RILP inhibited tumor growth by inhibiting the PI3K/AKT/mTOR pathway. Conclusion Our study revealed that the expression of RILP was associated with favorable prognosis of osteosarcoma and RILP inhibits proliferation, migration, and invasion and promotes autophagy in osteosarcoma cells via Grb10-mediated inhibition of the PI3K/AKT/mTOR signaling pathway. In the future, targeting RILP may be a potential strategy for osteosarcoma treatment.